A mapping of visual SLAM algorithms and their applications in augmented reality - Covolan, Joao Pedro Mucheroni [UNESP]; Sementille, Antonio Carlos [UNESP]; Sanches, Silvio Ricardo Rodrigues (Institute of Electrical and Electronics Engineers (IEEE), 2020)
The term visual SLAM defines the problem of build a map of an environment and perform location, simultaneously. In the augmented reality experience, we can apply SLAM techniques to insert virtual elements in the user's real-world view according to their observation point (location) and environment structure (mapping). In this work, we investigated the main algorithms of visual SLAM, and its applications in augmented reality. Here, we describe the key features of these algorithms and two taxonomies for SLAM techniques are proposed.
Um mapeamento de algoritmos de visual SLAM e suas aplicacoes em realidade aumentada
Keywords: augmented reality; visual SLAM; visual SLAM techniques